Abdominal aortic aneurysms: screening, epidemiology and open surgical repair. Issue 6 (June 2018) - Robertson, Vaux; Bown, Matt
Abstract: Abdominal Aortic Aneurysm (AAA) is a dilatation of the infra-renal abdominal aorta to greater than 3 cm. Population screening is offered to men in their 65th year in the UK. Patients with small AAAs (<5.5 cm) are entered into surveillance programs and should have cardiovascular risk factors managed aggressively. An AAA with ≥5.5 cm diameter should be considered for surgical repair to prevent rupture. Open surgical repair has proven to be a durable treatment for AAA and while less often performed than endovascular aneurysm repair (EVAR) it remains a common approach in the surgical management of AAA. While associated with higher short-term risks than EVAR, the long-term outcomes are similar and many younger patients have a preference for open repair as routine follow-up is not required.